Profile of Concept Understanding and Scientific Argumentation Skills on Genetic Material of Grade XII MIPA Students of SMA Laboratorium UM - Biruni, Iqbal Bilgrami; Suwono, Hadi; Muntholib, Muntholib (BIOEDUKASI, 2024)
Scientific argumentation skills as an intellectual practice can involve students in constructing and criticizing scientific ideas related to science literacy. The purpose of this study is to find out the scientific argumentation ability of high school students with different conceptual understandings. This study was designed as a survey involving students in grade XII of MIPA SMA Laboratorium UM. The results show that the highest average value of understanding the concept of genetic material was 87,22 and the lowest average value was 69,00. Indicator of scientific argumentation "claims and warrants" have an average value of 67.33; the "counterargument" indicator is 84.89; the "supportive arguments" indicator is 63.75; the "evidence" indicator is 83.19. The most appropriate solution to improve students' scientific argumentation skills is to apply an innovative learning model that involves argumentative dialogue in the classroom. Argumentation Driven Inquiry (ADI) is an argumentation and inquiry-based learning model that can be used as an alternative to empower students' scientific argumentation skills. On the other hand, students with low conceptual understanding scores managed to achieve the category of excellent scientific argumentation: good, enough, less, very little. This condition shows the importance of implementing innovative and argument-inquiry-based learning.